Mapping BRICS media - Nordenstreng, Kaarle; Thussu, Daya Kishan (Internationalizing media studies, 2015)
"Mapping BRICS Media brings together distinguished scholars from the BRICS nations to assess the effects of the exponential growth in media in some of the world's fastest growing major economies and examine how the emergence will impact on global media and communication.Transnational in scope and comparative in approach, the book will focus on significant and yet hitherto largely ignored developments in the globalization of media. By interrogating the relationship between the inter-BRICS media and media practices and perceptions, this volume will provide an accessible and comprehensive guide to the complex debates about the impact of the rise of the rest on the media globe"--